Prophetic Framework in Educational Evaluation: A Qualitative Study on Minimum Competency Assessment in Indonesia - Lismawati; Ramadhan, Alif Rizky; Astuti, Anita Puji (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2024)
Indonesia has long endeavored to establish and develop an evaluation method that can serve as the main reference across all educational levels and regions within the country. This effort has intensified following the release of the 2018 PISA assessment results, where Indonesia ranked low in several tested areas. One of the major policy changes introduced is the Minimum Competency Assessment (AKM), intended to become the primary method for evaluating learning outcomes in Indonesia. However, the national assessment still requires significant corrections and adjustments. This study aims to examine the application of the conceptual framework developed by Kuntowijoyo to refine the current assessment system and investigate how this framework can be authoritative without falling into authoritarianism in education. The research positions itself to offer recommendations from the perspectives of Islamic education and Islamic sociology regarding the Minimum Competency Assessment developed by the Ministry of Education. This study employs a qualitative methodology, utilizing a literature review and discourse analysis based on Kuntowijoyo’s prophetic social science. The findings of this study conclude that an assessment based on Kuntowijoyo’s conceptual framework can effectively embody the core objectives sought by the Ministry of Education.